2005
DOI: 10.1002/mc.20048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in oral squamous cell carcinoma

Abstract: Rapid advances in multimodality therapy have not significantly improved the overall 5-yr survival of oral cancer patients in the past two decades, thereby underscoring the need for molecular therapeutics. The development of new treatment strategies for more effective management of oral cancer requires identification of novel biological targets. Therefore, the aim of this study was to identify novel genes associated with oral tumorigenesis by comparing gene expression profile of oral squamous cell carcinomas (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 33 publications
8
72
0
3
Order By: Relevance
“…There are several studies performed in OSCCs from western countries (14,32,(38)(39)(40), and some of the genes found in our study to be differentially expressed correlate with findings from western countries. These include in particular COL4A1, COL1A1, MMP1, PLAU, SPARC, TNC and KRT19, with MMP1 and PLAU as the most frequent genes.…”
Section: Discussionsupporting
confidence: 79%
“…There are several studies performed in OSCCs from western countries (14,32,(38)(39)(40), and some of the genes found in our study to be differentially expressed correlate with findings from western countries. These include in particular COL4A1, COL1A1, MMP1, PLAU, SPARC, TNC and KRT19, with MMP1 and PLAU as the most frequent genes.…”
Section: Discussionsupporting
confidence: 79%
“…We further showed that increased expression of these two 14-3-3 isoforms may serve as an adverse indicator for prognosis of head and neck cancers (11). Notably, we identified and verified increased expressions of 14-3-3ζ transcripts in oral squamous cell carcinoma in comparison with normal oral epithelium using differential display (12,13).…”
Section: Introductionmentioning
confidence: 54%
“…In this analysis, 14-3-3z was clearly upregulated in human hepatocellular carcinoma, seminoma, pancreatic adenocarcinoma and several types of lung carcinoma (Figure 4). Similarly, studies on human stomach cancer (Jang et al, 2004), oral squamous-cell carcinoma (Arora et al, 2005) and breast cancer (Zang et al, 2004), have identified 14-3-3z among the most significantly increased proteins/genes in the tumours as compared to the corresponding normal tissues. Furthermore, 14-3-3z maps to human chromosome 8q23, a region frequently amplified in metastatic cancer (Tada et al, 2000;Ghadimi et al, 2003).…”
mentioning
confidence: 89%